Young Investigator. (January 2011) - Borges, Keyller Bastos; Bonato, Pierina Sueli
Supervisor''s supporting comments Keyller B Borges carried out his MS and PhD studies in toxicology under my supervision. During the time he spent in my laboratory, he worked on the development of analytical methods and studied the biotransformation of several drugs by fungi. Characteristics such as dedication, ability, initiative and dynamism had been the basis for the success of his projects developed under my supervision, resulting in several publications in prestigious periodics of the area. Therefore, I consider Dr Keyller highly capable for the development of activities in the area of bioanalysis.